KARAKTERISTIK BIOPELLET DARI CAMPURAN LIMBAH CANGKANG KEMIRI (Aleurites moluccana) DENGAN SERBUK KAYU JATI (Tectona grandis Linn) - Ilham Muziburrahman; Hairil Anwar; Andi Tri Lestari (Universitas Tanjungpura, 2023)
Biopellets are one of the alternative energies from biomass. The purpose of this study was to determine the physical properties and quality of biopellets from the combination of hazelnut shell raw materials and teak sawdust. The highest density was obtained in A4B4 treatment of 0.42 gr/cm3 and the lowest in A5B5 treatment of 0.26 gr/cm3. The highest water content of A3B3 treatment was 0.23% and the lowest in A1B1 treatment was 0.13%. The highest ash content of A1B1 treatment was 12.98% and the lowest was A4B4 treatment 5.28%.The highest level of flying substance A2B2 treatment was 32.73% and the lowest A4B4 treatment was 27.99%. The highest bound carbon in A4B4 treatment was 66.59% and the lowest in A1B1 treatment was 55.50%. The highest calorific value of A2B2 treatment is 17.85 MJ/Kg and the lowest is A1B1 treatment 17.21 MJ/Kg.Keywords: biopellet, candlenut shell, physical properties, quality, teak wood powderAbstrakBiopellet merupakan salah satu energi alternatif dari biomassa. Tujuan penelitian ini untuk mengetahui sifat fisis dan kualitas biopellet dari kombinasi bahan baku cangkang kemiri dan serbuk kayu jati. Diperoleh kerapatan tertinggi pada perlakuan A4B4 0,42 gr/cm3 dan terendah pada perlakuan A5B5 sebesar 0,26 gr/cm3. Kadar air tertinggi perlakuan A3B3 0,23% dan terendah pada perlakuan A1B1 0,13%. Kadar abu tertinggi perlakuan A1B1 12,98% dan terendah perlakuan A4B4 5,28%. Kadar Zat Terbang tertinggi perlakuan A2B2 32,73% dan terendah perlakuan A4B4 27,99%. Karbon terikat tertinggi pada perlakuan A4B4 66,59% dan terendah perlakuan A1B1 55,50%. Nilai kalor tertinggi perlakuan A2B2 17,85 MJ/Kg dan terendah perlakuan A1B1 17,21 MJ/Kg.Kata Kunci: biopellet, cangkang kemiri, sifat fisik, kualitas, serbuk kayu jati